The arboreal tiger beetles (Coleoptera: Cicindelidae) of Sri Lanka recorded from recent investigations - Abeywardhana, Lakmini; Mallawarachchi, Yashas; Dangalle, Chandima Deepani (Zootaxa, 2021)
Twenty-nine species of arboreal tiger beetles are found in Sri Lanka of which 23 species are endemic. However, records of species dates back to many years and systematic studies are lacking. Considering the high percentage of endemic arboreal tiger beetle species of the country, and the pressure on their arboreal habitats due to accelerated development activities, it is imperative that the group is studied and conservation practices are implemented. Therefore, the present study was conducted to record the arboreal tiger beetle species currently prevailing in the country, their locations, habitat types, morphometric and morphological characters. The study was conducted from August 2017 to September 2020 for a duration of three years. Arboreal tiger beetles were collected by hand picking when encountered during visual survey, in eighty-five locations in Sri Lanka. Specimens were identified using standard taxonomic keys. Locational data, habitat types, morphometric and morphological characters were recorded and all species were photographed. Arboreal tiger beetles were recorded from 22 locations which represented all climatic zones and provinces, and 14 districts of the country. Nine species of three genera, Tricondyla (3 species), Derocrania (5 species), Neocollyris (1 species), were identified and six of the species were endemic. Derocrania scitiscabra was the most common and widely distributed species encountered in the study and was found mainly occupying lands that were cultivated. Tricondyla gounellei that had been known only from Southern India was recorded for the first time in Sri Lanka.